"Inverse signaling" of the transmembrane chemokine CXCL16 contributes to proliferative and anti-apoptotic effects in cultured human meningioma cells. Issue 1 (December 2016) - Hattermann, Kirsten; Bartsch, Kareen; Gebhardt, Henrike; Mehdorn, H.; Synowitz, Michael; Schmitt, Anne; Mentlein, Rolf; Held-Feindt, Janka
Abstract Background Chemokines and their receptors play a decisive role in tumor progression and metastasis. We recently found a new signaling mechanism in malignant glioma cells mediated by transmembrane chemokines that we termed "inverse signaling". According to this hypothesis, soluble (s )- CXCL16 binds to the surface-expressed transmembrane (tm) - CXCL16, and induces signaling and different biological effects in the stimulated cells, so that the transmembrane ligand itself acts as a receptor for its soluble counterpart. Now, we hypothesized that "inverse signaling" viatm- CXCL16 might also take place in meningiomas, a completely different, benign tumor entity. Methods We used quantitative reverse-transcription polymerase chain reaction, immunocytochemistry and western blot to detect CXCL16 and CXCR6 in human meningioma cells isolated from 28 human meningiomas. Subsequently, we stimulated cultured humantm- CXCL16-positive, CXCR6-negative meningioma cells with recombinants- CXCL16 and analyzed binding, signaling and biological effects using RNAi silencing to verify specificity. Results In fact, cultured human meningioma cells considerably express CXCL16, but substantially lack CXCR6, the only known CXCL16 receptor. These receptor-negative cells could binds- CXCL16, and responded tos- CXCL16 application with activation of the intracellular kinases ERK1/2 und Akt. As a consequence, we observed increased proliferation and rescue of apoptosis of cultured meningioma cells. Since binding and signaling were abolished by siRNA silencing, we concluded thattm- CXCL16 specifically acts as a receptor fors- CXCL16 also in human meningioma cells. Conclusion These findings underline our recent report on the mechanism of inverse signaling as a broad biological process also observable in more benign tumor cells and contributing to tumor progression.